Effect of TiC particles on the mechanical properties of aluminium alloy metal matrix composites (MMCs). (2017) - Pandey, Utkarsh; Purohit, Rajesh; Agarwal, Pankaj; Dhakad, S.K.; Rana, R.S.
Abstract: Titanium carbide is the costly reinforcement nano powder mostly used in structural applications, aerospace, automobile industries and specific cutting tools where safety is main consideration factor and reasons are not difficult to understand as far as cost concerned. The primary objective in aircraft or anywhere is safety. In the present research the effect of titanium carbide particles on their mechanical properties with different aluminium matrix has been reviewed. The ultrasonic assisted stir casting is an economical and amenable process for medium to large scale production as compared to other methods such as powder metallurgy and spray forming. The objective of this paper is to study the current research and development in aluminum-based in situ and ex-situ composites by casting route. Very few work has been reported on nano TiC particulates synthesized with Al 6061 using ex-situ method. TiC particulates reinforced composites are attributed to tremendous bond reliability of TiC particulates with aluminium. Titanium carbide is proved to be a potential reinforcement for improved mechanical properties in Al MMCs.